Christocracy as a Theological Foundation: An Analysis of Leadership Authority in the Presbyterian-Synodal System - Merry Deiby Oroh (International Forum of Researchers and Lecturers, 2025)
The Presbyterian-Synodal system of church government is based on the ideal theological foundation of Christocracy, the confession that Christ is the sole Head of the Church who rules directly through His Word and Spirit. Theoretically, this model rejects hierarchy, affirms the parity of all ecclesiastical officers (ministers, elders, deacons) as servants, and views the local church council as a complete church (ecclesia completa). However, in historical and contemporary practice, a fundamental tension exists whereby this system consistently deviates into hierarchical and clerical practices. This deviation manifests as a hierarchy of office (clericalism) and a hierarchy of assemblies (Synod-centrism), where authority shifts from Christ to official figures and Synodal structures that are viewed as the